Rituximab maintenance for patients with aggressive B-cell lymphoma in first remission: results of the randomized NHL13 trial - Jaeger, Ulrich; Trneny, Marek; Melzer, Helen; Praxmarer, Michael; Nawarawong, Weerasak; Ben Yehuda, Dina; Goldstein, David; Mihaljevic, Bilijana; Ilhan, Osman; Ballova, Veronika; Hedenus, Michael; Hsiao, Liang-Tsai; et al. (Haematologica, 2015)
We investigated rituximab maintenance therapy in patients with diffuse large B-cell lymphoma (n=662) or follicular lymphoma grade 3b (n=21) in first complete remission. Patients were randomized to rituximab maintenance (n=338) or observation (n=345). At a median follow-up of 45 months, the event-free survival rate (the primary endpoint) at 3 years was 80.1% for rituximab maintenance versus 76.5% for observation. This difference was not statistically significant for the intent-to-treat population (likelihood ratio P=0.0670). The hazard ratio by treatment arm was 0.79 (95% confidence interval 0.57-1.08; P=0.1433). The secondary endpoint, progression-free survival was also not met for the whole statistical model (likelihood ratio P=0.3646). Of note, rituximab maintenance was superior to observation when treatment arms only were compared (hazard ratio: 0.62; 95% confidence interval 0.43-0.90; P=0.0120). Overall survival remained unchanged (92.0 versus 90.3%). In subgroup analysis male patients benefited from rituximab maintenance with regards to both event-free survival (84.1% versus 74.4%) (hazard ratio: 0.58; 95% confidence interval 0.36-0.94; P=0.0267) and progression-free survival (89.0% versus 77.6%) (hazard ratio: 0.45; 95% confidence interval 0.25-0.79; P=0.0058). Women had more grade 3/4 adverse events (P=0.0297) and infections (P=0.0341). Men with a low International Prognostic Index treated with rituximab had the best outcome. In summary, rituximab maintenance in first remission after R-CHOP-like treatment did not prolong event-free, progression-free or overall survival of patients with aggressive B-non-Hodgkin lymphoma. The significantly better outcome of men warrants further studies prior to the routine use of rituximab maintenance in men with low International Prognostic Index. This trial is registered under EUDRACT #2005-005187-90 and www.clinicaltrials.gov as #NCT00400478.
Keywords: výsledek terapie; Lymphoma, Follicular; analýza přežití; Rituximab; Male; Antineoplastic Combined Chemotherapy Protocols; následné studie; sexuální faktory; Intention to Treat Analysis; Lymphoma, Large B-Cell, Diffuse; Adult; Aged; dospělí; mužské pohlaví; senioři; rituximab; Survival Analysis; Follow-Up Studies; Treatment Outcome; senioři nad 80 let; lidé; ženské pohlaví; difúzní velkobuněčný B-lymfom; folikulární lymfom; Humans; Sex Factors; protokoly protinádorové kombinované chemoterapie; Aged, 80 and over; Female; lidé středního věku; indukce remise; analýza podle původního léčebného záměru; Middle Aged; Remission Induction